Identification of Early Citrus Black Spot Symptoms (Identificacíon de los Síntomas Iniciales de la Mancha Negra de los Cítricos) - Megan M. Dewdney; Jamie D. Burrow; Mark A. Ritenour (EDIS, 2018)
This identification sheet was designed to assist packinghouse employees to identify the early yet subtle symptoms of citrus black spot. Proper identification of citrus black spot prevents the rejection of international fruit shipments.